Pengaruh Penerapan Sistem E-Filling, Sanksi Perpajakan, Biaya Kepatuhan dan Pengetahuan Perpajakan Terhadap Kepatuhan WPOP pada KPP Pratama Badung Utara - Izra Syafira (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to empirically test the effect of the application of e-filling system, tax sanctions, compliance costs and tax knowledge on the compliance of private taxpayers. The method of analysis used in this study is multiple linear regression analysis. The method of sampling taxpayers using the slovin formula, with the taxpayer sample used is as many as 100 respoden. The sample determination method uses a simple random sampling method. The results of this study showed that variable application of e-filling (X1) positively and significantly affects the compliance of private taxpayers. This is evidenced by the significance result of 0.000<0.05. Tax sanctions (X2) have a positive and significant effect on the compliance of private taxpayers. This is evidenced by the significance result of 0.001<0.05. Compliance costs (X3) have a positive and significant impact on the compliance of private persons taxpayers. This is evidenced by the significance result of 0.000<0.05. Tax knowledge (X3) has a positive and significant effect on the compliance of private taxpayers. This is evidenced by the significance of 0.000<0.05.